2011
DOI: 10.1002/anie.201007987
|View full text |Cite
|
Sign up to set email alerts
|

Splitting Water with Cobalt

Abstract: The future of energy supply depends on innovative breakthroughs regarding the design of cheap, sustainable, and efficient systems for the conversion and storage of renewable energy sources, such as solar energy. The production of hydrogen, a fuel with remarkable properties, through sunlight-driven water splitting appears to be a promising and appealing solution. While the active sites of enzymes involved in the overall water-splitting process in natural systems, namely hydrogenases and photosystem II, use iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
1,076
0
12

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,294 publications
(1,101 citation statements)
references
References 232 publications
(461 reference statements)
13
1,076
0
12
Order By: Relevance
“…It is shown that the materials containing Co and/or V (typically the oxides) are potential catalysts for OER [33]. We then studied the OER performance of the samples in 1 mol L −1 KOH.…”
Section: Electrochemical Performance For Oermentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the materials containing Co and/or V (typically the oxides) are potential catalysts for OER [33]. We then studied the OER performance of the samples in 1 mol L −1 KOH.…”
Section: Electrochemical Performance For Oermentioning
confidence: 99%
“…The cobalt (Co), as a typical LTM, is promising in HER due to its relatively low cost and the activity for the reduction of H + [33]. Generally, single Co metals have shown poor activity and stability for HER.…”
Section: Introductionmentioning
confidence: 99%
“…This family of complexes has become of renewed interest in the past few years, following reports in 2005 [1,2] and 2007 [3,4,5] of their promising hydrogen-evolving catalytic capability. Today, cobaloximes, and the related diimine-dioxime cobalt complexes [6,7,8,9], are recognized as some of the most efficient molecular catalysts for electro-and photo-catalytic hydrogen evolution [10,11,12]. These compounds are known to be powerful nucleophiles in their reduced Co(I) state.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are known to be powerful nucleophiles in their reduced Co(I) state. It is accepted that the catalytic cycle for hydrogen evolution proceeds via protonation of the Co(I) species, yielding a Co(III)-H hydridocobaloxime intermediate that, after further reduction to the Co(II)-H state, can evolve dihydrogen through either protonation of the hydride moiety or bimolecular reductive elimination [1,2,3,4,5,10,11,6,13,14,15,16,17,18].Recent reports from the groups of Muckerman [19], and Jiang [21] have addressed aspects of the catalytic activity of these compounds using quantum chemical approaches and confirm the role of the Co(I) species. Experimentally, the spectroscopic signatures of Co(I) intermediates have been observed during the course of electro-and photo-catalytic experiments [4,5,22], and the Co(I) species [14,23,24,9], and its protonated Co(III)-H form [25,26,27] Figure 1).…”
mentioning
confidence: 99%
“…The FeFe hydrogenase is the most active catalyst for H 2 evolution, with a fascinating turnover frequency (TOF) up to 6000À9000 s À1 . 16,17 Since the structure of FeFe hydrogenase was resolved in 1998 (as shown in Figure 4), 35,36 45,46 For its high activity and relatively low working potential, this type of complex has been recognized as a functional hydrogenase mimic. 47,48 To achieve lightdriven H 2 evolution, hydrogenase mimics were combined with light harvesters.…”
Section: Hybrid Photocatalysts For H 2 Evolutionmentioning
confidence: 99%